2019
DOI: 10.1186/s40795-019-0293-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of culinary interventions (cooking classes) on dietary intake and behavioral change: a systematic review and evidence map

Abstract: Background: Culinary interventions (cooking classes) have been used to improve the quality of dietary intake and change behavior. The aim of this systematic review is to investigate the effects of culinary interventions on dietary intake and behavioral and cardiometabolic outcomes. Methods: We conducted a systematic review of MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, Cochrane Database of Systematic Reviews, and Scopus for comparative studies that evaluated culinary interventions to a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 45 publications
4
69
2
2
Order By: Relevance
“…Previous adolescent cooking interventions have measured markers of diet quality such as nutrient intakes or consumption of food groups [61], although the COOK Study is the first we know of to apply a diet quality index. Our findings concur with the many other interventions which reported improved aspects of diet quality [61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous adolescent cooking interventions have measured markers of diet quality such as nutrient intakes or consumption of food groups [61], although the COOK Study is the first we know of to apply a diet quality index. Our findings concur with the many other interventions which reported improved aspects of diet quality [61].…”
Section: Discussionmentioning
confidence: 99%
“…Previous adolescent cooking interventions have measured markers of diet quality such as nutrient intakes or consumption of food groups [61], although the COOK Study is the first we know of to apply a diet quality index. Our findings concur with the many other interventions which reported improved aspects of diet quality [61]. Taste preference and availability are two of the biggest predictors of adolescents' fruit and vegetable intakes [62] and may have been influenced by the intervention, as other cooking interventions have found increased taste preferences for fruit and vegetables [20,28].…”
Section: Discussionmentioning
confidence: 99%
“…The habit of preparing meals at home seems to be associated with healthy eating behaviors [10,11]. Thus, interventions aimed at developing cooking skills can contribute to healthy eating [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews of community level cooking interventions found significant improvements in attitudes, cooking self-efficacy, and healthy dietary intake and participation in cooking interventions [18,19]. However, no significant outcomes are reported for cardiometabolic risk factors, including blood pressure and body mass index (BMI) within these reviews.…”
Section: Gaps In the Literaturementioning
confidence: 99%